Influence of AFM Tip Temperature on THF Hydrate Stability: Theoretical Model and Numerical Simulation - Li Peng (Scanning, 2019)
Atomic force microscopy (AFM) indentation is widely used to determine mechanical parameters of various materials. However, AFM tip may lead to phase transition of the cold sample in the region of contact area. It is a long-standing challenge that low-temperature phase-change materials (e.g., ice and hydrate) are hardly characterized by AFM, especially for clathrate hydrates. Here, with theoretical analysis and numerical simulation, we investigated the temperature influence of AFM tip on the tetrahydrofuran (THF) hydrate stability. At first, a steady-state model of heat conduction was established between a v-shaped probe and THF hydrate sample. The temperature of the tip was estimated at different laser spot positions and laser intensities. Through numerical simulation, the heat loss by air convection is less than 1% of the total laser heat, and the influence of ambient air on the AFM probe temperature can be neglected. Meanwhile, the local temperature in the region of contact area was also calculated at the THF hydrate temperature of 0°C, -10°C, -20°C, and -30°C. We found out that the AFM tip causes the cold THF hydrate to melt. The thermal melting thickness decreases with the reduction of laser intensity and THF hydrate temperature. On the contrary, it is positively correlated with the thickness of liquid-like layer on THF hydrate surface and is also linearly increased with the contact radius. This indicates that the thermal melting continues as the press-in depth of the tip into THF hydrate increases. The local temperature rises when the tip touches the THF hydrate. It is easier for THF hydrate to be melted by an external pressure. In addition, the proposed model may be useful for guiding force tests on low-temperature phase-change materials by the AFM indentation.